Knowledge and attitude towards epilepsy among undergraduate students of a private university in Kajang, Malaysia - H’ng, Gilbert Yung Han (2020)
Epilepsy is one of the oldest conditions in the world, a total of 50 million or 0.5% of the world population suffers from epilepsy. The incidence rate of epilepsy is 49 per 100,000 population. Knowledge and attitude are important to reduce stigma and discriminations towards epilepsy. The aim of this study is to determine the knowledge and attitude of undergraduate students towards epilepsy in a private university in Kajang, Malaysia. A cross-sectional, quantitative analytical survey was carried out in a private university in Kajang, Malaysia. A total of 277 undergraduate students currently pursuing a degree course in the selected private university were recruited through quota sampling. Self-administered online questionnaire consisting of 3 sections, socio-demopraphic data, knowledge towards epilepsy and attitude towards epilepsy was used for data collection. Data obtained was analysed using descriptive and analytical analysis. The level of knowledge towards epilepsy among the respondents was relatively high with 41.5% having good knowledge, and only 4% with poor knowledge. The level of attitude towards epilepsy was very positive among the respondents at 92%. Level of knowledge was significantly associated with the faculty of the respondents with a p-value of 0.014. Significant association between the level of attitude with the faculty of the respondents was identified with p-value of 0.049. Respondents from medical and health sciences field had better level of knowledge and attitude towards epilepsy. The level of knowledge towards epilepsy was relatively high but there was still concerning presence of false beliefs. The level of attitude towards epilepsy among undergraduate students was positive. Health promotion campaign are recommended to increase the awareness and decrease stigma and discrimination towards people with epilepsy.